A Wake Model for the Prediction of Propeller Performance at Low Advance Ratios - Ye Tian; Spyros A. Kinnas (International Journal of Rotating Machinery)
A low order panel method is used to predict the performance of propellers. A wake alignment model based on a pseudounsteady scheme is proposed and implemented. The results from this full wake alignment (FWA) model are correlated with available experimental data, and results from RANS for some propellers at design and low advance ratios. Significant improvements have been found in the predicted integrated forces and pressure distributions.